PERANGKAT LUNAK PENDISTRIBUSIAN GAS LPG MENGGUNAKAN METODE ZACHMAN DAN METODOLOGI SCRUM - amelia hani (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
ABSTRACT The demand for LPG gas distribution from suppliers to gas agents in Indonesia are increasing. Many of the suppliers, which one of them is PT. Bhakti Mingasutama complained that this increase in demand affected the performance and effectiveness of gas distribution to the Agent. The lack of the role of information technology that is applied in the process of LPG gas distribution in PT. Bhakti Mingasutama as the supplier made many things hampered such as lack of monitoring or monitoring of LPG gas sales and delivery data to agents, LPG gas ordering was still done manually by means of the agent visiting the Supplier and recording transactions carried out by the sales supplier manually. This is what underlies the research to build a system that can facilitate Suppliers and Agents in buying, selling, managing sales and distribution data, sending or taking LPG gas without needing to spend more time making transactions. By using the Zachman Framework method to support the analysis of data requirements and the requirements for making the system as well as the Scrum methodology to help manage the system work timeline, this system is expected to be beneficial for both parties in gas distribution, especially in the North Jakarta area. Keywords: Gas Distribution, Zachman Framework, Scrum Methodology